PENGARUH PENGEMBANGAN KARIER DAN LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN PADA PERUSAHAAN PT GRAHA MITRA LESTARINDO DI JAKARTA SELATAN - Febrian, Muhammad; Yanuarti, Maghfiroh (Journal of Research and Publication Innovation, 2024)
The purpose of this research is to determine the influence of career development and work environment on employee performance at PT Graha Mitra Lestarindo in South Jakarta. The method used is quantitative. The partial and simultaneous sampling technique used saturated sampling and obtained a sample of 50 respondents. Data analysis uses validity tests, reliability tests, classical assumption tests, regression analysis, correlation coefficients, coefficients of determination and hypothesis testing. The results of this research are that career development has a significant effect on employee performance with a coefficient of determination value of 51.0% and the hypothesis test obtained t count > t table or (7.045 > 2.010). The work environment has a significant effect on employee performance with a coefficient of determination value of 62.4% and the hypothesis test obtained t count > t table or (8.923 > 2.010). Career Development and Work Environment simultaneously have a significant effect on Employee Performance with the regression equation Y = 6.458+ 0.155X1 + 0.3576X2. The coefficient of determination value is 64.1% while the remaining 35.9% is influenced by other factors. Hypothesis testing obtained calculated F value > F table or (41.724 > 2.800).